Oral Management by a Full-Time Resident Dentist in the Hospital Ward Reduces the Incidence of Pneumonia in Patients with Acute Stroke - Kenichiro Ozaki; Satoshi Teranaka; Haruka Tohara; Shunsuke Minakuchi; Satoru Komatsumoto (International Journal of Dentistry)
Background. A full-time dentist was assigned to a ward at our hospital to improve the quality of oral healthcare for hospitalized patients. A dental care system (DCS) was created to facilitate the collaboration between the full-time dentist and the nursing department. Objective. To investigate the effects of DCS implementation on the incidence of pneumonia in patients with acute stroke. Methods. This retrospective cohort study comprised 945 hospitalized acute stroke patients categorized into three groups: pre-, during-, and post-DCS. The DCS comprised dentist-led lectures and practical sessions, oral assessments, standardized oral care techniques, and information on the procedures for nurse-requested dental intervention. Data were extracted from the Japanese Diagnosis Procedure Combination database and medical records. The attributes of the patients, incidence of pneumonia, and number of patients who requested dental intervention were determined. Results. The odds ratios of pneumonia onset were 3.16 (95% confidence interval [CI], 1.65–6.05; P=0.001) in the pre-DCS and 2.80 (95% CI, 1.48–5.31; P=0.002) in the during-DCS group compared with the post-DCS group, thereby confirming the effect of DCS on the incidence of pneumonia. The number of dental requests in the post-DCS group was noted to be higher than that in the pre-DCS group (P=0.002). Conclusion. Oral management by a full-time dentist was found to be effective in reducing the incidence of pneumonia in patients with acute stroke. To implement the best oral care practices in the hospital wards, the full-time dentist should work as a member of the medical team.